Pelatihan Basic Life Support And Disaster Management Di Era New Normal - Aristiyanto Aristiyanto; Ahmad Kholid; Muhammad Imron Rosyidi; Eko Susilo; Guntur Ratih Prestifa Herdinata; Fredy Eko Setiawan (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2022)
This community service activity aims to provide an understanding for high school students on the importance of basic training for students in providing assistance to disaster or emergency victims in order to prevent death or organ damage so that their productivity can be maintained equally before the disaster or emergency event occurs. Such as accidents or natural disasters can occur anywhere and anytime, such as traffic accidents, household accidents, work accidents, and so on. Handling these problems is aimed at providing basic life support so that it can save lives and minimize organ damage and disability of sufferers. In order to achieve the purpose of this service, the following steps are required; a) coordinate with schools, b) gather information from partners by conducting field observations, c) carry out outreach, outreach, and education for partners. This service is carried out over 6 months which includes; Initial observations exploring existing problems and then studying them to provide problem-solving, followed by initial seminars and preparation, counseling, and reporting. The service was held with theoretical material: a) disaster management, b) basic life support, c) first aid in an accident. The results of the dedication are; 1) increasing knowledge of basic life support, and 2) increasing knowledge of disaster management, for training participants. So it can be concluded that basic life support and disaster management training has an impact on increasing the knowledge, understanding and ability of service partners in dealing with disaster emergencies in the KY Ageng Giri Banyumeneng High School environment, Mranggen, Demak Regency.ABSTRAKKegiatan pengabdian ini bertujuan untuk memberikan pemahaman bagi siswa sekolah menegah atas mengenai pentingnya pelatihan dasar bagi siswa/ pelajar sekolah dalam memberikan pertolongan pada korban bencana atau gawat darurat guna mencegah kematian atau kerusakan organ sehingga produktivitasnya dapat dipertahankan setara sebelum terjadinya bencana atau peristiwa gawat darurat yang terjadi. Seperti kecelakaan atau bencana alam dapat terjadi dimana saja dan kapan saja, seperti halnya kecelakaan lalu lintas, kecelakaan rumah tangga, kecelakaan kerja, dan sebagainya. Penanganan masalah tersebut ditujukan untuk memberikan bantuan hidup dasar sehingga dapat menyelamatkan nyawa dan meminimalisir kerusakan organ serta kecacatan penderita. Dalam rangka mencapai tujuan pengabdian ini, diperlukan langkah-langkah sebagai berikut; a) berkoordinasi dengan sekolah, b) menggali informasi dari mitra dengan melakukan observasi lapangan, c) melaksanakan penyuluhan, sosialisasi, dan edukasi bagi mitra. Pengabdian ini dilaksanakan dalam 6 bulan yang meliputi; observasi awal menggali masalah yang ada kemudian dikaji untuk diberikan pemecahan masalah, dilanjutkan seminar awal dan persiapan, penyuluhan, dan pelaporan. Pengabdian yang diselenggarakan dengan materi teori: a) disaster management, b) basic live support, c) pertolongan pertama pada kecelakaan. Hasil pengabdian adalah; 1) meningkatnya pengetahuan basic life support, dan 2) meningkatnya pengetahuan management disaster,bagi peserta pelatihan. Sehingga dapat disimpulkan bahwa pelatihan basic life support dan management disaster berdampak pada meningkatnya pengetahuan, pemahaman dan kemampuan mitra pengabdian dalam menghadapi keadaan kedaruratan bencana di lingkungan sekolah SMA KY Ageng Giri Banyumeneng, Mranggen Kabupaten Demak.